Relationships between muscle fibre characteristics and physical performance capacity in trained athletic boys - Mero, A.; Jaakkola, L.; Komi, P. V. (Journal of Sports Sciences, 1991)
Boys (11-13 yr, N = 18) from different sports (4 endurance runners, 7 tennis players, 4 weightlifters, 3 sprinters) were divided into two groups according to a "fast" group (M = 59% Type II fibers) and a "slow" group (M = 60.6% Type I fibers). A variety of tests were performed. Fibers were divided into (a) Type I slow-twitch oxidative, (b) Type IIA fast-twitch oxidative, and (c) Type IIB fast-twitch glycolytic. Few significant differences were revealed. Reaction time to sound and choice reaction time were faster for the fast group and it also had a greater rate of force development. A weak significant relationship between Type II fiber area and blood lactate levels (r = .53) was revealed. There were no differences between running velocity, maximal oxygen uptake, or anaerobic characteristics. The similarity in aerobic capacity stemmed from the training program of the boys (general endurance within each sport). The Type IIA fibers made up the inherent difference by adapting to oxidative work. It was shown that even though the "fast" boys inherited 66.5% more Type II fibers, a greater percentage of them switched to oxidative functioning so that between the groups the fast group had 77.3% and the slow group 83.2% of fibers functioning oxidatively. This suggests that in young boys, the adaptability of fibers allows individuals to perform a variety of tasks, particularly of an endurance nature. Implication. In young boys, the adaptability of the inherited fiber distributions to different types of training makes measures of aerobic or anaerobic capacity relatively useless as a performance predictor. However, reaction time and power development rates may discriminate between fast- and slow-twitch dominant pubescent boys. This is about all that can be used to identify capacity talent that will not be revealed in a current sporting performance.